(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to explore the constraints and solutions in the utilization of the Learning Management System (LMS) ’Bebas UMPO’ by students of the Mathematics Education Study Program at FKIP Universitas Muhammadiyah Ponorogo. The approach used is qualitative exploratory with a case study design, involving semi-structured interviews, documentation, and observation as data collection techniques. Research findings show that there are three main categories of constraints faced, namely technical constraints (such as limitations in networks and devices), pedagogical (the lack of interactivity in the material), and cultural (low motivation and readiness for independent learning among students). In response to these constraints, the proposed solutions include improving digital infrastructure, training lecturers in technology-based content development, and strengthening students’ digital literacy. Additionally, the integration of innovative learning media such as videos, interactive forums, and visual content is also recommended to enhance the effectiveness of using LMS. This finding emphasizes the importance of a systemic approach that involves technology, pedagogy, and academic culture in supporting the transformation of digital learning. This research contributes to the development of more adaptive and contextual local LMS, as well as providing practical recommendations for higher education institutions in optimizing the use of learning technology.